1995
DOI: 10.1002/mus.880180219
|View full text |Cite
|
Sign up to set email alerts
|

How helpful is thoracic paraspinal EMG in HAM/TSP?

Abstract: Results of electrophysiologic studies are frequently abnormal in HAM/TSP when lower limb somatosensory evoked potential (LLSEP) studies are employed.' Our previous electrophysiologic studies in HAM/TSP pointed to lesions below the cervical spinal cord. '*' Electrophysiologic findings such as these, may be helpful in diagnosis but are not specific for HAM/TSP. The present paraspinal (PSP) electromyographic (EMG) studies were performed based on the assumption that the procedure might assist in identifying lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Despite the fact that axonal changes happen early in disease in HAM/TSP 49,50 , the demyelination process as well as the clinical course described throughout the years resembles multiple sclerosis 53,54 . MEP abnormalities in paraspinal muscles were found consistently abnormal, the lesion being more bilateral in HAM/TSP compared to multiple sclerosis; however, the small sample of patients investigated precluded advancing conclusions about the paraspinal involvement of HAM/TSP 30,45 . In any event, CMCT, and likely, conduction velocity to paraspinal muscles obtained with TMS, may be added to the laboratory investigations suggested elsewhere 9,45,53,54 in helping differentiate these two disorders, mostly in places where they could overlap in the general population [55][56][57][58] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite the fact that axonal changes happen early in disease in HAM/TSP 49,50 , the demyelination process as well as the clinical course described throughout the years resembles multiple sclerosis 53,54 . MEP abnormalities in paraspinal muscles were found consistently abnormal, the lesion being more bilateral in HAM/TSP compared to multiple sclerosis; however, the small sample of patients investigated precluded advancing conclusions about the paraspinal involvement of HAM/TSP 30,45 . In any event, CMCT, and likely, conduction velocity to paraspinal muscles obtained with TMS, may be added to the laboratory investigations suggested elsewhere 9,45,53,54 in helping differentiate these two disorders, mostly in places where they could overlap in the general population [55][56][57][58] .…”
Section: Discussionmentioning
confidence: 89%
“…These abnormal, albeit consistent, findings on HAM/TSP fit well with the abnormalities around the mid-thoracic and lumbar regions found in neuroimaging and pathological investigations described elsewhere on this disorder 44 . In these latter studies, it has been demonstrated that the main lesion is atrophy of lateral columns at around the thoracic level 45,46 .…”
Section: Discussionmentioning
confidence: 97%
“…Because peripheral nerve conduction velocities were within normal limits, we concluded that the central conduction time was prolonged. Notably, prolonged central conduction time has been reported to be a possible finding in HAM/TSP [ 16 , 17 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…39,48 Electrodiagnostic studies also demonstrate denervation within the lower thoracic paraspinal muscles in HAM/TSP patients and support the presence of anterior horn cell or ventral root involvement, although such electromyogram (EMG) changes could also be seen in polymyositis. 49 Despite an apparent ''predisposition'' to anterior horn cell/ventral root involvement, case reports exist, but no large series, and may reflect prevalent but ''subclinical'' involvement that is often masked by more prominent clinical deficits secondary to the myelopathy or additional neuromuscular involvement. Such an example can be found in three patients with HTLV-1 and evidence of polymyositis on examination, electrodiagnostic testing, and muscle biopsy who were also found to have evidence of anterior horn cell involvement.…”
Section: Als-like Manifestationsmentioning
confidence: 99%